The perceptions of HIV Positive patients (ART patients) on ART and Treatment Supporters with regard to their role towards ART adherence, at ART clinics in the Intermediate Hospital Oshakati, Namibia - Tuhadeleni, Olivia Ningeninawa (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.